PEMINDAHAN IBU KOTA NEGARA INDONESIA DI MEDIA DARING: ANALISIS WACANA KRITIS (THE RELOCATION OF INDONESIA’S CAPITAL CITY IN ONLINE MEDIA: A CRITICAL DISCOURSE ANALYSIS) - Agustina, Agustina (Universitas Lambung Mangkurat, 2024)
AbstractThe Relocation of Indonesia’s Capital City In Online Media: A Critical Discourse Analysis. The relocation of the nation's capital has become a controversial topic and has sparked widespread debate in online media. The main issue examined in this study is the form of support and rejection of the policy of relocating the capital city and the reasons behind it. This study uses a qualitative approach with Norman Fairchlough's critical discourse analysis method to identify different views in online media. The data sources come from articles on Kompas.com, Tempo.com, and Suaraislam.com on January 18 and 19, 2022. The findings of this study indicate that Kompas.com supports the policy of relocating the nation's capital city with emotional support, appreciation and information related to political, economic, historical and environmental aspects. In contrast, Tempo.com and Suaraislam.com show rejection, focusing on legal, political, economic and environmental aspects. Rejection on Tempo.com is conveyed through suggestions, comments and reasons for rejection, while Suaraislam.com expresses rejection using words such as